Cyclically Loaded Copper Slag Admixed Reinforced Concrete Beams with Cement Partially Replaced with Fly Ash - Avudaiappan-, S (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
Generally, the concrete with higher strength appears to produce brittle failure more easily. However, the use of mineral admixture can help in enhancing the ductility, energy dissipation, and seismic energy in the designed concrete. This paper presents energy absorption capacity, stiffness degradation, and ductility of the copper slag (CS) admixed reinforced concrete with fly ash (FA) beams subjected to forward cyclic load. The forward cyclic load was applied with the help of servo-hydraulic universal testing machines with 250 kN capacity. Twenty-four beams with a size of 100 mm × 150 mm × 1700 mm made with CS replaced for natural sand from 0% to 100% at an increment of 20%, and FA was replaced for cement from 0% to 30% with an increment of 10% were cast. Beams are designed for the grade of M30 concrete. Based on the preliminary investigation results, compressive strength of the concrete greatly increased when adding these two materials in the concrete. Normally, Grade of concrete can change the behaviour of the beam from a brittle manner to be more ductile manner. So, in this work, flexural behaviour of RC beams are studied with varying compressive strength of concrete. Experimental results showed that the RC beam made with 20% FA and 80% CS (FA20CS80) possesses higher ultimate load-carrying capacity than the control concrete beam. It withstands up to 18 cycles of loading with an ultimate deflection of 60 mm. The CS and FA admixed reinforced concrete composite beams have excellent ultimate load carrying capacity, stiffness, energy absorption capacity, and ductility indices compared to the control concrete beam. © 2022 by the authors. Licensee MDPI, Basel, Switzerland.
Keywords: monotonic load; forward cyclic load; stiffness; energy absorption and ductility